Oil on water - Habila, Helon 1967- (Penguin Books, 2011)
"From the desks of Nigeria's newsrooms, two journalists are recruited to find the kidnapped wife of a British oil engineer. Zaq, an infamous and ageing hack, knows the score, but Rufus, who is keen, young and eager to get noticed, has no idea what he's let himself in for. Journeying into the oil-rich regions of the Niger Delta, where militants and corporations rule, and life is cheap but death even cheaper, Rufus uncovers a world far darker and more corrupt than he ever imagined."
"First published by Hamish Hamilton 2010"--T.p. verso
Keywords: Petroleum industry and trade / Fiction; Journalists / Nigeria / Fiction; Kidnapping victims / Fiction; Corruption / Nigeria / Fiction; Britin; Erdölkonzern; Journalist; Entführung; Suche; Niger River Delta Region (Nigeria) / Fiction; Nigeria; Fiktionale Darstellung